Effect of different remineralization agents on the optical properties of bleached enamel - Aslıhan Ertemür; Başak Yazkan (BMC Oral Health)
Abstract Background The aim of this study was to evaluate the effect of different remineralization agents applied immediately after bleaching on the colour stability, whiteness index and whiteness index difference of enamel. Methods One hundred enamel samples from bovine incisors were divided into two groups for at-home and in-office bleaching. The samples were further divided into five subgroups: (1) Acidulated phosphate fluoride (APF), (2) Casein phosphopeptide amorphous calcium phosphate fluoride (CPP-ACPF), (3) Calcium glycerophosphate, fluoride (CaGP, F), (4) Hydroxyapatite, fluoride (HAp, F), and (5) control. After treatment, all samples were stained with red wine. Color measurements were taken at baseline, after bleaching, after remineralization, and after staining using a dental spectrophotometer. Optical parameters included L*, a*, b*, CIEDE2000 color difference (ΔE00), whiteness index for dentistry (WID), and whiteness index difference (ΔWID). Statistical analyses were performed with Kruskal Wallis, Friedman, and Dunn tests. Results Color and whiteness differences after bleaching were statistically similar between in-office and at-home bleaching (p > 0.05). Remineralization protocols had no significant effect on enamel color or whiteness across all groups (p > 0.05), but significant differences were found between the CPP-ACPF, CaGP, F, HAp, F, and control groups (p < 0.05). Conclusion Application of remineralization agents after bleaching was found to be ineffective on color and whiteness change of bleached enamel. Remineralization agents containing HAp, CPP-ACP and CaGP, respectively, were found to be more successful in terms of color stability.